Proliferation of Mesenchymal Stem Cells in Carbonate Apatite-Chitosan Scaffolds in Bone Tissue Engineering Techniques - Aqsa Sjuhada Oki; Maretaningtias Dwi Ariani (Cumhuriyet University, 2019)
Objectives: Chitosan (poly-1,4-D-glucosamine) become popular as bone graft material. It has a high biocompatibility and biodegradability, non-toxic, bacteriostatic, and has good adsorption properties. It also enhances the proliferation and differentiation of the osteoblast cell cultures. However, chitosan also has a weakness for cell adhesion and the lack of sufficient bone formation capabilities. To improve it, we tried to develop a chitosan scaffolds that combine with carbonate apatite (CA), which has excellent biocompatibility properties of the tissues of the human body. Purpose: to make the carbonate apatite-chitosan scaffolds (CA-ChSs) and evaluate CA-ChSs from the standpoint of cell proliferation using mesenchymal stem cells (MSCs). Materials and Methods: Porous chitosan matrix was made by using the lyophilization technique. ChSs containing chitosan powder was made by the following procedure. 100, 150, 200, and 400 mg of chitosan powder was dissolved in 5 ml of 2% acetic acid at room temperature. To make CA-ChSs, ChSs containing 200 mg of chitosan powder was chosen. Ultraviolet radiation was then performed for 2 hours. CA-ChSs structure was observed by a scanning electron microscope (SEM). Proliferation of MSCs in CA-ChSs evaluated at days 1, 3, 5 and 7.Results:This study demonstrated that CA-ChSs containing 200 mg of chitosan powder and 50 mg CA has a three-dimensional structure that is porous and attachment powder CA in the pores and absorbance values were increased from the examination day 1 until day 7. Conclusion:Based on these results, it is expected CA-ChSs may be candidates for bone graft material in tissue engineering techniques.